Analysis Of Seaport Safety In Nigeria: Case Of Apapa Port Complex Lagos (Maritime Park: Journal of Maritime Technology and Society, 2023)
The aim of this study is to assess the seaport operational safety of Apapa port Lagos. Primary data were collected using survey for the analysis. The study utilized Logit model and Multi-Criteria Decision Analysis to analyse the data collected from` the seaport. In running the analysis, SPSS software version 24.0 was used to analyse the data. The result from the Logit model shows that there is a high significant relationship between the dependent and independent variables tested in the study. This means that there is need for improvement in the area of safety at the port. Furthermore, the multi-criteria decision analysis result also shows various sections and their corresponding weights and ranks with a level of improvement that will be help to step up or enhance the safety variables during port operation. The study recommends that the seaport should be carrying out constant safety study from time to time to increase the safety and security levels of the seaport as recommended by the IMO
Keywords: Safety; Security; Seaport; Terminal